2023
DOI: 10.21037/tp-23-339
|View full text |Cite
|
Sign up to set email alerts
|

Short-term change of tibial torsion in children with spastic cerebral palsy after selective dorsal rhizotomy

Rui Wang,
Wenbin Jiang,
Min Wei
et al.

Abstract: Background Spastic cerebral palsy (CP) is a prevalent cause of motor dysfunction in children, with patients often experiencing secondary musculoskeletal deformities, including tibial torsion. This study aimed to investigate the short-term effect of selective dorsal rhizotomy (SDR) on tibial torsion in children with spastic CP. Methods We conducted a retrospective review of children with spastic CP who underwent SDR at the Department of Neurosurgery, Shanghai Children’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…We read with interest Wang et al ’s article about a retrospective study of 143 pediatric patients with cerebral palsy who underwent selective dorsal rhizotomy (SDR) between July 2019, and November 2022 and were examined pre- and post-operatively ( 1 ). It was found that SDR significantly reduced the muscle tone of the lower limb muscle groups, the range of motion of the joints in the lower limbs and the transmalleolar angle (TMA) increased after surgery, and the preoperative internal tibial torsion before SDR decreased and changed to a normal angle post-operatively in 21% of limbs ( 1 ). Improvement with SDR was observed particularly in younger patients with low muscle tone in the hamstring muscles ( 1 ).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…We read with interest Wang et al ’s article about a retrospective study of 143 pediatric patients with cerebral palsy who underwent selective dorsal rhizotomy (SDR) between July 2019, and November 2022 and were examined pre- and post-operatively ( 1 ). It was found that SDR significantly reduced the muscle tone of the lower limb muscle groups, the range of motion of the joints in the lower limbs and the transmalleolar angle (TMA) increased after surgery, and the preoperative internal tibial torsion before SDR decreased and changed to a normal angle post-operatively in 21% of limbs ( 1 ). Improvement with SDR was observed particularly in younger patients with low muscle tone in the hamstring muscles ( 1 ).…”
mentioning
confidence: 99%
“…It was found that SDR significantly reduced the muscle tone of the lower limb muscle groups, the range of motion of the joints in the lower limbs and the transmalleolar angle (TMA) increased after surgery, and the preoperative internal tibial torsion before SDR decreased and changed to a normal angle post-operatively in 21% of limbs ( 1 ). Improvement with SDR was observed particularly in younger patients with low muscle tone in the hamstring muscles ( 1 ). It was concluded that SDR has the potential to increase TMA in cerebral palsy patients and that anterior tibial torsion improves after SDR especially when patients are young and have low muscle tone in the hamstring muscles ( 1 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We would like to extend our gratitude to Dr. Walter Strobl and colleagues for their thoughtful and constructive critique of our recent clinical study titled “Short-term change of tibial torsion in children with spastic cerebral palsy after selective dorsal rhizotomy”, which was published in the Translational Pediatrics ( 1 ).…”
mentioning
confidence: 99%